Down-regulation of NCED leads to the accumulation of carotenoids in the flesh of F1 generation of peach hybrid - Song, Haiyan; Liu, Junhong; Chen, Chaoqun; Zhang, Yao; Tang, Wenjing; Yang, Wenlong; Chen, Hongxu; Li, Mengyao; Jiang, Guoliang; Sun, Shuxia; Li, Jing; Tu, Meiyan; et al. (Frontiers in Plant Science, 2022)
Flesh color is one of the most important target traits in peach[Prunus persica (L.) Batsch] breeding. In this study, the white flesh peach Changsong Whitepeach (WP-1), ‘Xiacui’ and their hybrid F1 generation were used as the research materials. Two white-fleshed peach parents (Changsong Whitepeach×Xiacui ) were crossed, and the color separation of white flesh and yellow flesh appeared in the hybrid F1 peach. Metabolome analysis showed that carotenoid content was the cause of the difference in flesh color of peach hybrid F1 generation. Decreasing of β-carotene and β-cryptoxanthin in flesh of BF1 and increasing of β-cryptoxanthin oleate, rubixanthin laurate and violaxanthin myristate in flesh of HF1, was responsible for the difference in carotenoid accumulation between the two groups. Transcriptome analysis showed that compared with the white-fleshed peach hybrid F1 generation, ZEP and CCD8 were significantly up-regulated and down-regulated in the core-hardening stage of yellow-fleshed peach hybrid F1 generation, respectively. While the expression of NCED was significantly down-regulated in the whole fruit development stage of the peach yellow-fleshed hybrid F1 generation. Therefore, according to transcriptome and metabolome results, it was surmised that NCED was down-regulated at all stages of the peach yellow-fleshed hybrid F1 generation, which inhibited the breakdown of the violaxanthin derivatives and further promoted the accumulation of carotenoids, resulting in a yellow flesh trait. Therefore, NCED may be the key gene controlling fruit color traits in peach hybrid F1 generation. In this study, the methods of targeted metabolomics and transcriptomics were used to jointly explore the mechanism of controlling the fruit color of the peach hybrid F1 generation, which would help to identify the key genes for differences in carotenoid accumulation and provide a reference for the breeding of yellow peach.